Fluorescence Caused by Pseudomonas in the Mucus of Helix Aspersa Muller - Hugh C. Rawls; Patrick J. Bernardi; Joan F. White (Hello World!, 1972)
The yellow fluorescence observed when mucus from Helix aspersa is exposed to ultraviolet light was first reported by Turchini (1926) and later mentioned by Fischer and Saddy (1949); Turchini mentioned in a footnote that Oerrien had communicated o-rally with him regarding the phenomenon. Although the cause of such fluorescence in land snails has been undetermined until recently, Derrien and Turchini (1925) earlier had suggested a bacterial origin. Subsequently, papers by Rawls and Yates 0971) and Rawls and Baum (1971) indicated a relationship between pseudomonad bacteria and fluorescence in the mucus of certain endodontid and polygyrid snails. Most recently, Baum and Rawls (1972) established the role of pseudomonads in the production of fluorescent pigments in the mucus of Anguispira kochi (Pfeiffer), and Rawls, Baum and Yates (1972) described fluorescence caused by pseudomonads in the mucus of Bulimulus inscendens Binney. We now wish to report that the distinctive fluorescence which is characteristic of the mucus of Helix aspersa likewise is caused by the occurrence of specific pigments produced by pseudomonad bacteria.